A RP-HPLC-UV Method with Solid Phase Extraction for Determination of Cefepime in Total Nutrient Admixtures: Application to Stability Studies - S. Iqbal, Muhammad; B. Bahari, Muhammad; Darwis, Yusrida; Venkatesh, Gantala; W. Gillani, Syed; H. Khan, Amer; Sheshala, Ravi (Current Pharmaceutical Analysis, 2012)
A simple, specific and selective RP-HPLC-UV method with Solid Phase Extraction (SPE) was developed for the quantification of cefepime in Total Nutrient Admixtures (TNAs). Chromatographic separation was achieved on C18 column using a mobile phase consisting of a mixture of ammonium acetate, acetonitrile and methanol. The flow rate was set to 0.9 mL min-1 and the wavelength was 257 nm. The analyte was extracted from TNAs by using SPE technique. Cefepime calibration curve was linear over a concentration range of 100-1400 μg mL-1 with a correlation coefficient of ≥0.9994. The intraday accuracy and precision were ≤-4.76% and ≤3.12% respectively. The interday accuracy and precision were ≤-3.90% and ≤4.29% for respectively. The method was successfully applied to stability studies of cefepime in the presence of micronutrients together with low and high concentrations of macronutrients in TNAs. Cefepime was degraded by 42.84% and 58.81 % at room temperature (25±2°C) after 72 hours in low and high macronutrient concentration formulations of TNAs respectively. Cefepime first order degradation rates for low and high macronutrient concentration formulations of TNAs were -0.0032 and -0.0049 hr-1 respectively. These results indicated a higher rate of degradation in TNA formulations with high concentrations of macronutrients.
Keywords: TNAs